M. Bernal, Black Athena. The afroasiatic roots of classical civilization. Volume 1: The Fabrication of Ancient Greece 1785-1985. London, Free Association Books, 1987. 575 pp,. figs. - López Castro, José L. (Gerión. Revista de Historia Antigua, 1991)
Sin resumen